The Reality of Teaching Practices of the Faculty Members at the Islamic University of Madinah Under Conditions of the Pandemic of Coronavirus "COVID-19" - الحربى، عبدالله بن عبدالمحسن (جامعة الأمير سطام بن عبدالعزيز, 2022)
هدفت هذه الدراسة إلى التعرف على واقع الممارسات التدريسية لأعضاء هيئة التدريس في الجامعة الإسلامية بالمدينة المنورة في ظل ظروف جائحة فيروس كورونا (COVID- 19) خلال الفصل الدراسي الثاني ٢٠٢٠ م. استخدمت الدراسة المنهج الوصفي كأسلوب لها. وكانت أداة جمع البيانات عبارة عن استبيان مكون من ٣٣ فقرة غطت أربعة أبعاد: بيئة التدريس، وأساليب وطرق التدريس، وطرق تقويم الطلاب، والعقبات التي تعترض التدريس عبر الإنترنت. وزعت الاستبانة عشوائيا على مجتمع الدراسة وأجاب عليها ١٨٥ عضو هيئة تدريس من جميع كليات الجامعة. استخدمت الدراسة الإحصائيات الوصفية واختبار ANOVA للحصول على نتائجها. أظهرت نتائج الدراسة أن جميع أعضاء هيئة التدريس في الجامعة الإسلامية في الأبعاد الكلية لممارسات التدريس كانوا على درجة عالية (M= 3.65, SD= 0.481740) كما قارنت الدراسة بين المشاركين وفقا للمعهد أو الكلية التي يدرسون بها. وقد أشارت النتائج إلى وجود فروق ذات دلالة إحصائية في ممارسات التدريس بين أعضاء هيئة التدريس بالجامعة الإسلامية تعزى إلى الكلية التي يدرسونها فيها (Sig= 0.000). وقدمت الدراسة العديد من التوصيات بالاعتماد على نتائجها. This study aimed at investigating the reality of teaching practices for the faculty members; at the Islamic University of Madinah; under conditions of the pandemic of Coronavirus (COVID-19) during the second term 2020. The study used a descriptive approach as a method. The tool of collecting data was a questionnaire consisted of 33 items covered four dimensions: teaching environment, styles and methods of teaching, methods of evaluating students, and obstacles to teaching online. The questionnaire was distributed randomly and responded by 185 faculty members of all university colleges. The study also utilized descriptive, and ANOVA test statistics to obtain its results. The study results revealed that all faculty members at Islamic university on the whole dimensions of teaching practices were in a high degree (M = 3.65, SD = .48174). The study also compared participants according to their colleges they teach in. There are statistically significant differences in teaching practices among teaching staff at Islamic university due to the college they teach in it (Sig. = .000). Finally, the study presented many recommendations dependently on its results.
Keywords: فيروس كورونا "كوفيد-19" -- التعليم عن بعد -- التعليم الإلكتروني -- طرائق التدريس -- المؤسسات الجامعية